A wireless sensors suite for Smart Grid applications - Grilo, António (2013)
This paper presents a demonstrator of a Wireless Sensor and Actuator Network (WSAN) for Smart Grid applications, developed in the context of project WSAN4CIP. This WSAN is formed by WSAN nodes equipped with sensors and a wireless radio interface, which monitor key parameters of power grid equipments belonging to the Medium Voltage (MV) and Low Voltage (LV) segments. The measurements are reported to the SCADA system and constitute the basis of both safety and security services to improve the power grid distribution dependability. This paper describes the hardware of the sensor nodes and presents the respective performance results, attesting the feasibility of the proposed solutions.